Recent Developments in Research and Treatment of Testicular Cancer: Highlights from Oncologic Congresses in 2009 - TİNAY, İLKER (ELSEVIER, 2010)
Objectives: This paper summarizes new findings on testicular cancer presented at the European Society for Medical Oncology and American Society of Clinical Oncology annual meetings in 2009. Methods: Data were discussed during the seventh meeting of the European Association of Urology Section of Oncological Urology in January 2010. Selection of data was based on expert experience. Results: An important molecular study on metastasized and nonmetastasized seminoma tissues showed that presence of metastases can be predicted with 100% specificity based on an 85-gene expression signature. Invasion of the rete testis and age (<30 yr) represented high-risk factors for patients with clinical stage I testicular seminoma, independent from the treatment selected. Long-term results (8 yr) of standard bleomycin (B), etoposide (E), and cisplatin (P) therapy for good prognosis germ cell tumors (GCTs) concluded a continuing survival benefit, with 3B90E500P proving itself as the standard of care. A new individualized treatment protocol based on tumor marker decline in metastatic nonseminomatous germ cell testicular cancer is highly encouraging in all risk groups. But a phase 3 randomized trial with administration of front-line high-dose chemotherapy in poor-prognosis GCTs did not improve treatment outcome. The 20-yr experience with two cycles of PEB showed that late toxicity is rare; the two principal effects of the treatment were higher triglyceride and lower testosterone levels in this group of patients. Two important studies investigated surgery versus surveillance for postchemotherapy residual masses in patients with metastatic nonseminomatous GCTs (NSGCTs). They both concluded that residual masses <15 mm after primary chemotherapy for metastatic NSGCT may be managed without surgery; no clear conclusions are drawn for larger masses, and further studies are needed. Retrospective analysis of complications of postchemotherapy residual tumor resection showed that full bilateral resection is not necessary in all cases and resection field should be adapted to the localization of disease and size of the mass to minimize complications. The popular question of whether to use open or laparoscopic surgery for retroperitoneal masses remained unanswered. The results of a short follow-up study (15 mo) favored open surgery for better operating time and lower complication rate and laparoscopic surgery for shorter hospital stay. There was no difference in the rate of distant metastases. Conclusions: New data presented at these meetings may contribute to improved management of testicular cancer. (C) 2010 European Association of Urology. Published by Elsevier B. V. All rights reserved.
Keywords: Chemotherapy; Germ cell tumor; Laparoscopic; Retroperitoneal lymph node dissection; Surveillance; Testicular cancer; GERM-CELL TUMORS